The chromaticity of s-bridge graphs and related graphs - Xu, Shaoji; Liu, Jinjie; Peng, Yeehock (Elsevier, 1994)
The graph consisting of s paths joining two vertices is called s-bridge graph. In this paper, we discuss the chromaticity of some families of s-bridge graphs, especially 4-bridge graphs, and some graphs related to s-bridge graphs.